Peningkatan Kapasitas Pengelolaan Dana Desa di Kecamatan Bulango Ulu - Maliki, Alinda; Hamim, Udin; Rachman, Ellys (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Village fund management perspective refers to the level of human resource capacity and is influenced by various things. The aim of this research is to analyze capacity building and factors that influence village fund management in Bulango Ulu District, Bone Bolango Regency. This research method is descriptive qualitative. The results of this research show that performance capacity, personal capacity and supporting service facilities are not optimal. Furthermore, 3 factors that influence capacity building are human resources that are not yet competent, village government organizational commitment is good, and community participation where the community is less involved in managing and supervising village funds.